Perbandingan faktor resiko aorta abdominal dilatasi pada penderita penyakit jantung koroner dengan menggunakan ekokardiografi - Yuke Sarastri; Andre Pasha Ketaren; Nizam Akbar; Sutomo Kasiman; Zulfikri Mukhtar; Tengku Winda Ardini; Rosmaliana dr; Abdullah Afif Siregar (Fakultas Kedokteran USU, 2012)
Background : Patients with coronary artery disease share common risk factors as abdominal aortic aneurysm (AAA), in which screening for AA dilatation is recommended. Transthoracic echocardiography (TTE) may offer the opportunity to evaluate the cardiac function and to screen for AA dilatation during the same examination.Aims : This study aimed to compare risk factors for abdominal aortic dilatation with abdominal aorta index in patients with coronary artery disease, and to evaluate the feasibility of AA dilatation screening at bedside using TTE in population with CAD. Methods : This is a cross-sectional study of patients with CAD. The abdominal aortic was measured at the end of a regular TTE performed in consecutive patients admitted in coronary care unit of Haji Adam Malik Hospital Medan using an echocardiography machine.Results : We enrolled 75 patients with mean age 56 (SD 10) years. Dilatation of abdominal aortic was observed in 21 patients (28%). From the analysis obtained a significant relationship between history of acute myocardial infarction with dilatation abdominal aorta (P = 0.04).Conclusion : Overall, the prevalence of dilatation of abdominal aortic increased with age and history of AMI. In regard to the simplicity, screening for AA dilatation during TTE may be of value for patients with CAD, especially in elder patients. Keywords : echocardiography; dilatation of abdominal aortic; coronary artery disease